Intercultural Communication and Teaching Russian to International Students at Language Summer Courses - Romanov, Yu.; Snegurova, T. A. (Национальный исследовательский Мордовский государственный университет, 2017)
Introduction: the article considers the content and methods of teaching Russian as a foreign language at language summer courses with due account to (as a form of study-abroad training) the motives of intercultural communication. The specifics of teaching Russian to international students in the cultural field of Ukraine is revealed. The timeliness of the study is determined by constantly increasing academic mobility of students and the need for the development of modern educational technologies. The main purpose of the article is to present an integrated approach to Russian as a foreign language teaching at language summer courses, when cultural needs of the trainees and the motives of intercultural communication are considered. Materials and Methods: teaching methodology draws on specific methods of teaching Russian as a foreign language and models of intercultural competence development. Educational materials for practical teaching of the Russian language are presented; qualitative and quantitative methods to research intercultural communication motives (written questionnaires and interviews on key topics) are used. Results: through working with the learners of language courses – students of Austrian universities – the data on the learners’ motivation factors, the most relevant topics for intercultural dialogue, some important aspects of Russian grammar, and also the data on the most popular knowledge about Ukraine are obtained and carefully analysed. The analysis of the obtained data, carried out by the authors of the study, allowed to optimise the content of the educational process and to incre ase its effectiveness. Discussion and Conclusions: teaching Russian to foreigners, showing a keen interest in the cultural values of Ukraine, suggests a parallel formation of intercultural competence based on understanding the local cultural realities. The presented approach to RFL teaching within the framework of the language summer courses provides not only a strong uptake of linguistic material by international students and considerable improvements in their level of proficiency in the Russian language, but also a significant enhancement of the intercultural competence of the trainees on the basis of a variety of teaching techniques and active intercultural communication of international students with native Russian language speakers when working in tandem. The practical significance of the study is determined by the fact that the proposed approach to Russian as a foreign language teaching may find wide applicatio n in the training of foreigners at language summer courses; research perspectives are determined by the continuous development of this form of education and the increased importance of intercultural compete nce in the practice of cultural interaction.

Введение: в статье рассматриваются содержание и методика обучения русскому языку как иностранному на летних языковых курсах, отражающих мотивы межкультурной коммуникации. Раскрыта специфика преподавания русского языка студентам-иностранцам в культурном поле Украины. Актуальность исследования определяется возрастающей академической мобильностью студентов и необходимостью разработки современных образовательных технологий для их обучения. Цель статьи – представить комплексный подход в преподавании русского языка как иностранного на летних языковых курсах, при котором учитываются культурные запросы обучаемых и мотивы межкультурной коммуникации. Материалы и методы: методологическим обоснованием настоящего исследования являются частная методика преподавания русского языка как иностранного и модели развития межкультурной компетенции. Представлены учебные материалы для практического преподавания русского языка; использованы качественные и количественные методы исследования мотивов межкультурной коммуникации (письменные опросы и устные интервью по ключевым темам). Результаты исследования: в процессе работы со слушателями языковых курсов – студентами австрийских университетов – получены и изучены данные о факторах мотивации учащихся, наиболее значимые для них темы межкультурного диалога, важные аспекты русской грамматики, а также данные о наиболее востребованных знаниях об Украине. Анализ полученных данных, проведенный авторами исследования, позволил оптимизировать содержание учебного процесса и повысить его эффективность. Обсуждение и заключения: обучение русскому языку иностранцев предполагает параллельное формирование их межкультурной компетенции на основе понимания местных культурных реалий. Представленный подход к преподаванию русского языка как иностранного в рамках программы летних языковых курсов обеспечивает не только прочное усвоение языкового материала студентами-иностранцами и существенное улучшение их уровня владения русским языком, но и значительное повышение межкультурной компетенции обучаемых на основе применения разнообразных обучающих технологий и активной межкультурной коммуникации иностранных студентов с носителями русского языка при работе в тандеме. Практическое значение исследования определяется тем, что предлагаемый подход может найти широкое применение при обучении иностранцев на летних языковых курсах; перспективы исследования обусловлены непрерывным развитием данной формы обучения и повышением значимости межкультурной компетенции в практике культурного взаимодействия.
Межкультурная коммуникация и преподавание русского языка иностранным студентам на летних языковых курсах
Keywords: intercultural communication; intercultural competence; Russian as a foreign language; methods of teaching a second language; tandem language learning; language summer courses; межкультурная коммуникация; межкультурная компетенция; русский язык как иностранный; изучение языка в тандеме; летние языковые курсы